VISUAL APPLICATION OF BIG chili DISEASE USING VISUAL BASIC 6.0. - Ridwan Ridwan (Jurnal Sistem Informasi, 2005)
Applications are programs designed specifically to work or solve problems - special problems. With this approach the knowledge-based program was established to provide an information and solutions to society atapun hobbyists who want to know about chili plants are exposed to a large variety of diseases. With the use of special besifat applications that analyze large chili disease by showing a picture of the disease itself and chili along with information - information such as the causes, symptoms, and control of diseases such chili, then the author tries to make the Visual application of the disease this great chili by using programming language Visual Basic 6.0.Keywords: Applications, Visual, Chili disease.